Extensive mucocutaneous, oesophageal and otic lichen planus secondary to nivolumab therapy. Issue 1 (20th November 2020) - Ferguson, L.; Ho, B.; Weir, J.; Francis, N.; West, K.; Rathbone, B.; Larkin, J.; Heelan, K.
Abstract: We report a 73‐year‐old female with metastatic renal cell carcinoma who developed a widespread lichenoid reaction following nivolumab treatment. The timeline of the reaction strongly correlated with the nivolumab treatment and subsequent cessation. Our patient had cutaneous, mucosal, otic, ophthalmic and oesophageal involvement, demonstrating the potentially extensive nature of lichenoid reactions to anti‐programmed cell death receptor‐1 (anti‐PD1) therapies. Although lichenoid reactions to anti‐PD1 therapies are now well recognized, there have been no previous reports of otic or oesophageal involvement in the literature. Although cutaneous lichenoid reactions do not tend to be severe or treatment limiting, more widespread systemic lichenoid reactions are challenging to manage, particularly in the context of malignancy. This very unusual case highlights the importance of considering involvement beyond the skin in all lichenoid skin reactions.